1996
DOI: 10.1007/bf02396241
|View full text |Cite
|
Sign up to set email alerts
|

Population genetics and gene variation in screwworms (Diptera: Calliphoridae) from Brazil

Abstract: Allozyme variation in New

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0
3

Year Published

2002
2002
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 17 publications
1
4
0
3
Order By: Relevance
“…Teresina Caproni et al, 1998;Silva et al, 2005a, b;Lopes-Costa et al, 2008;Fresia et al, 2014;Mastrangelo et al, 2014 PR Carambeí, Colombo, Guarapuava, Jataizinho, Jundiaí Sul, Loanda, Mangueirinha, Maria Helena, Maringá, Nossa Senhora das Graças, Nova Esperança, Pato Branco, Paraíso do Norte, Sarandi, Tuneiras Oeste Caproni et al, 1998;Chicarelli et al, 2002;Gealh et al, 2009;Kotze et al, 2009;Lyra et al, 2009Lyra et al, , 2010Silva et al, 2011;Costa et al, 2012;Bergamo et al, Oliveira, 1980;D'Almeida, 1983;Muniz et al, 1995;Sanavria & Prata, 1996;Taylor et al, 1996;Caproni et al, 1998;Figueiredo et al, 2002Figueiredo et al, , 2006Passos et al, 2002;Cramer-Ribeiro et al, 2002a,b, 2003Oliveira et al, 2006;D'Almeida & Fraga, 2007;Marquez et al, 2007;Mendes-de-Almeida et al, 2007;Deleito & Moya-Borja, 2008;Ferraz et al, 2008Ferraz et al, , 2010aRodrigues-Guimarães et al, 2008;Pires, 2008;Batista-da-Silva et al, 2009;Correia et al, 2010;Ferraz et al, 2010a, b;Souza CP et al, 2010a;Souza JR et al, 2010b;Batista-da-Silva et al, 2011a, b, c, 2012…”
Section: State Municipalities Reference Pimentioning
confidence: 99%
“…Teresina Caproni et al, 1998;Silva et al, 2005a, b;Lopes-Costa et al, 2008;Fresia et al, 2014;Mastrangelo et al, 2014 PR Carambeí, Colombo, Guarapuava, Jataizinho, Jundiaí Sul, Loanda, Mangueirinha, Maria Helena, Maringá, Nossa Senhora das Graças, Nova Esperança, Pato Branco, Paraíso do Norte, Sarandi, Tuneiras Oeste Caproni et al, 1998;Chicarelli et al, 2002;Gealh et al, 2009;Kotze et al, 2009;Lyra et al, 2009Lyra et al, , 2010Silva et al, 2011;Costa et al, 2012;Bergamo et al, Oliveira, 1980;D'Almeida, 1983;Muniz et al, 1995;Sanavria & Prata, 1996;Taylor et al, 1996;Caproni et al, 1998;Figueiredo et al, 2002Figueiredo et al, , 2006Passos et al, 2002;Cramer-Ribeiro et al, 2002a,b, 2003Oliveira et al, 2006;D'Almeida & Fraga, 2007;Marquez et al, 2007;Mendes-de-Almeida et al, 2007;Deleito & Moya-Borja, 2008;Ferraz et al, 2008Ferraz et al, , 2010aRodrigues-Guimarães et al, 2008;Pires, 2008;Batista-da-Silva et al, 2009;Correia et al, 2010;Ferraz et al, 2010a, b;Souza CP et al, 2010a;Souza JR et al, 2010b;Batista-da-Silva et al, 2011a, b, c, 2012…”
Section: State Municipalities Reference Pimentioning
confidence: 99%
“…Krafsur & Whitten (1993) examined isozyme loci in 11 Mexican populations and reported that screwworm populations in Mexico belonged to a single panmitic population. Taylor et al (1996) also used isozyme loci to study two Brazilian populations and compared the results with previous data from Costa Rica (Taylor & Peterson, 1994) and partial data from Mexico (Krafsur & Whitten, 1993), also reporting that NWS represented a single panmitic population. By contrast, subsequent analyses of Brazilian populations, using different types of molecular markers in both the mitochondrial and nuclear genomes, suggested a reduced gene flow between interconnecting structured populations (Infante‐Vargas & Azeredo‐Espin, 1995; Infante‐Malachias et al , 1999; Azeredo‐Espin & Lessinger, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Blow flies of the family calliphoridae are distributed worldwide and some of the spices belonging to this family are known to be causative agents of animal tissue myiasis and transmission of enteric pathogens and parasites causing severe loss to live stoke (El-Azazy, 1989). Enzyme electrophoresis has contributed a great deal to elucidate genetic differences in calliphorids (Bush and Neck 1976 , Whitten 1980, Richardson et al 1982,Krafsur and Whitten 1993, Taylor and Peterson 1994, Taylor et al 1996, Wallman and Adams,1997,2001). However in the genus Chrysomya genetic variation has been analysed only by using microsatellite markers in Chrysomya albiceps (Torris and Azeredo-Espin, 2008) and C.Putoria (Rodrigues et al 2009) from Brazil.…”
Section: Introductionmentioning
confidence: 99%